Factors of Students’ Willingness and Unwillingness to Speak English in the Classroom - Kozi Ramli; Jumatul Hidayah; Sarwo Edy; Farida Esmianti (Universitas Bengkulu, 2021)
One of the goals of EFL education is to enhance students’ willingness to communicate (WTC) and to reduce their unwillingness to communicate (UWTC) so that students can consistently take part in English communication. Accordingly, this study aimed to investigate the factors of English students’ WTC and UWTC in the classroom context. This study applied a descriptive qualitative method by involving eighteen students from English department at State Islamic Institute of Curup as the participants. Of those students, nine of them were those of WTC group, and other nine students were those of UWTC group. They were split in such a way according to their values of speaking subjects and resting upon their lecturer’s consideration. The data were collected from interviews and analyzed using an interactive model. The findings revealed that the factors of students’ WTC covered classroom, teacher’s supports, personality, and self-confidence. Subsequently, the factors of students’ UWTC consisted of linguistic problems such as lack of English vocabularies, poor grammatical competence, and poor English pronunciation. Besides, there were also some non-linguistic factors such as psychological problems, low self-confidence, and anxiety. Further studies are expected to probe into the factors of WTC and UWTC by adopting both realistic and naturalistic worldviews as well as incorporating more multicultural participants to reveal more comprehensive information as desirable.